2016
DOI: 10.1016/j.matdes.2016.07.089
|View full text |Cite
|
Sign up to set email alerts
|

Origins of residual stress in thin films: Interaction between microstructure and growth kinetics

Abstract: Thin films can develop large residual stresses during their growth that significantly impact their performance. Therefore, there is a need to understand how the stress is related to the developing film structure and underlying kinetic processes. In this work, we describe measurements of stress and the corresponding grain structure during electrodeposition of Ni and Cu films. For Ni deposition, the grain size stays nearly constant during growth and the stress reaches a nearly constant steady-state. For Cu depos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(38 citation statements)
references
References 28 publications
3
34
0
Order By: Relevance
“…3(b) : after a tensile maximum of 400 MPa, the stress rapidly decreases and becomes compressive, and reaches a constant value of −150 MPa (0 V) and −130 MPa (−130 V) with further film thickening (above 100 nm). The observation of a CTC behavior in the early stages of growth is consistent with literature data on stress evolution in Cu polycrystalline films 29 31 , though the critical thickness for film continuity and post-coalescence compressive stress magnitudes may vary depending on the kinetics and energetics of the deposition process 32 .
Figure 3 In situ intrinsic stress measurements during thin film growth.
…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…3(b) : after a tensile maximum of 400 MPa, the stress rapidly decreases and becomes compressive, and reaches a constant value of −150 MPa (0 V) and −130 MPa (−130 V) with further film thickening (above 100 nm). The observation of a CTC behavior in the early stages of growth is consistent with literature data on stress evolution in Cu polycrystalline films 29 31 , though the critical thickness for film continuity and post-coalescence compressive stress magnitudes may vary depending on the kinetics and energetics of the deposition process 32 .
Figure 3 In situ intrinsic stress measurements during thin film growth.
…”
Section: Resultssupporting
confidence: 90%
“…S1 ) 42 . The presence of V-shaped columns suggests that grain size changes primarily at the surface 31 and that bulk diffusion is rather limited. Another evidence of surface diffusion is noticed from the evolution of the intrinsic stress at the end of the deposition (see Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is suggested that the energetic ion bombardment by increasing Cu target power does not all the times generate an increased tendency of compressive stress during deposition process. This phenomenon can be explained by the addition of Cu, which otherwise can be from a buffer area, leading to generating stress relief in the coatings [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…The cracking phenomena of the Mo 6 film started to be recognized after 4 days of the dry process at the ambient conditions. The stabilization of the Mo 6 film was partially limited because the evaporation of acetone will create a residual stress, which break the hydrogen bonding between the cluster nanoparticles containing the Mo 6 6 cluster network [38,39]. The cracking point is grown from the tiny grain boundary, which is generated by the separation of the cluster phase and solvent phase.…”
Section: Resultsmentioning
confidence: 99%